CAMAC/MBD interface for the VAX data acquisition facility at theKFUPM Energy Research Laboratory - Abdel-Aal, R.E. (1989)
The authors describe the CAMAC/MBD (microprogrammable branch driver) data acquisition interface used with the VAX 11/785 computer system at the Energy Research Laboratory (ERL) of King Fahd University of Petroleum and Minerals, Dhahran, Saudia Arabia. An ERL-developed automatic LAM (look-at-me) multiplexer module is described. Details of a simple and efficient scheme for the acquisition of multiparameter data are highlighted, and performance results are given. The hardware uses fast CAMAC analog-to-digital converter modules with constant conversion time. This has considerably simplified the interface hardware and allowed higher data rates to be acquired at lower values of deadtime in comparison with similar installations